Strengthening the Role of the Young Generation as the Influencers to Accelerate the Implementation of Green Economy: A Co-Creation Value Perspective - Maya Maria; Nihan Lanisy; Ginta Ginting (Journal of International Conference Proceedings, 2022)
ABSTRACT The role of the green economy is very important, where the fulfillment of needs does not sacrifice the goals of sustainable consumption and production as well as resource efficiency. Indonesia has made a National Action Plan (RAN) to implement the 12th principle in the Sustainable Development Goals, known as Responsible Consumption and Production (RCP) aimed at improving production processes and consumption practices to reduce resource consumption, waste generation, and emissions throughout the life cycle of processes and products. RCP requires citizen involvement about community, increased awareness, willingness to pay, and environmental-friendly lifestyle. This research is intended to analyze the role of the Young Generation to become Influencers (through co-creation of values) so that they can encourage the implementation of good practices as green consumers. To gain insights on people’s willingness to participate in green economy, preliminary research has been conducted involving 229 respondents. A model was constructed to identify the antecedents of willingness to participate. The antecedents were Attitude, Perceived Behavioral Control and Behavior. Descriptively, the field findings can explain the behavior and willingness to participate of the younger generation in green economy practices. The findings of the preliminary research can be used as the basis for proposing a more predictive model using the role of influencers as a moderating variable that intervene in the influence of behavioral intention on willingness to participate. Keywords: Behavior, Willingness to participate, SDG, Influencers, Co-creation of Value.